Enhancing Students’ Speaking Skills through Digital Storytelling: A Mixed-Methods Study - Wihdatun Nisa; Zulfa Sakhiyya (Universitas Islam Negeri Palopo, 2025)
This study investigates the effectiveness of digital storytelling techniques in improving English speaking skills among students at MA Mamba'ul Ulum. The research addresses the problem of low speaking proficiency and limited student participation in English language learning. The study employed a pre-experimental design with one group pretest-posttest, involving 24 students from class XI. Data collection was conducted through speaking tests and questionnaires to measure students' speaking abilities and gather perceptions from teachers and students. The implementation of digital storytelling followed five structured stages: warming-up, viewing, comprehension check, retelling, and individual presentation.